The Political Management of the Gay Community from the Appraisal and Ideational Meanings in Chilean Cyberpress Texts [la Gestión Política Gay Desde Los Significados Valorativos E Ideacionales en Textos de Ciberprensa Chilena] - Araya-Seguel, C (Univ Nacional de Educacion a Distancia (UNED), 2022)
This article offers a possibility of theoretical-methodological synergy for addressing different social problems. This is a work that explores the participation of the gay community in the social world configured in Chilean cyberpress texts between 2012-2017. The exploration is carried out from the theoretical-methodological articulation of the sociosemiotic APPRAISAL and IDEATION systems assigned to functional systemic linguistics to illustrate the relationship between social change and discursive change. The discursive analysis from these systems reveals that the gay community represented in the corpus constitutes an agent of social transformation, because it denounces homophobic violence and defends the victims, questions political and religious authorities, promotes changes and legal reforms and is recognized as political interlocutor before the events produced. © 2022 Universidad Nacional de Educacion a Distancia. All rights reserved.